Sperm-carried IGF2 downregulated the expression of mitogens produced by Sertoli cells: A paracrine mechanism for regulating spermatogenesis? - Cannarella, Rossella; Mancuso, Francesca; Arato, Iva; Lilli, Cinzia; Bellucci, Catia; Gargaro, Marco; Curto, Roberto; Aglietti, Maria C.; La Vignera, Sandro; Condorelli, Rosita A.; Luca, Giovani; Calogero, Aldo E. (Frontiers in Endocrinology, 2022)
Insulin-like growth factor 2 (IGF2) mRNA is present in human and mouse spermatozoa. However, it is unknown whether the IGF2 protein is expressed in human spermatozoa and, if so, its possible role in the cross-talk between germ and Sertoli cells (SCs) during spermatogenesis. To accomplish this, we analyzed sperm samples from four consecutive Caucasian men. We found that the IGF2 protein was present in each of the samples. IGF2 appeared as a cytoplasmic protein localized in the equatorial and post-acrosomal segment and with a varying degree of expression in each cell. To understand its role during the spermatogenetic process, porcine SCs were incubated with increasing concentrations (0.33, 3.33, and 10 ng/mL) of recombinant human IGF2 (rhIGF2) for 48 hours. Subsequently, the experiments were repeated by pre-incubating SCs with the non-competitive insulin-like growth factor 1 receptor (IGF1R) inhibitor NVP-AEW541. The following outcomes were evaluated: 1) Gene expression of the glial cell-line derived neurotrophic factor (GDNF), fibroblast growth factor 2 (FGF2), and stem cell factor (SCF) mitogens; 2) gene and protein expression of follicle-stimulating hormone receptor (FSHR), anti-Müllerian hormone (AMH), and inhibin B; 3) SC proliferation. We found that IGF2 significantly downregulated GDNF gene expression in a concentration-dependent manner. FGF2 and SCF were downregulated only by the highest concentration of IGF2. Similarly, IGF2 downregulated the FSHR gene and FSHR, AMH, and inhibin B protein expression. Finally, IGF2 significantly suppressed the SC proliferation rate. All these findings were reversed by pre-incubation with NVP-AEW541, suggesting an effect mediated by the interaction of IGF2 with the IGFR. In conclusion, we found that the IGF2 protein is expressed in human spermatozoa. IGF2 downregulates the gene expression of the GDNF, FGF2, and SCF mitogens physiologically released by the SCs to promote gonocyte proliferation and spermatogonial fate adoption, FSHR gene and protein expression, AMH, and inhibin B secretion by SCs as well as their in vitro proliferation rate. These findings suggest the presence of paracrine regulatory mechanisms acting on the seminiferous epithelium during spermatogenesis, by which germ cells can influence the amount of mitogens released by the SCs, their sensitivity to FSH, and their rate of proliferation.